2017
DOI: 10.1371/journal.pbio.2003143
|View full text |Cite
|
Sign up to set email alerts
|

Task relevance modulates the behavioural and neural effects of sensory predictions

Abstract: The brain is thought to generate internal predictions to optimize behaviour. However, it is unclear whether predictions signalling is an automatic brain function or depends on task demands. Here, we manipulated the spatial/temporal predictability of visual targets, and the relevance of spatial/temporal information provided by auditory cues. We used magnetoencephalography (MEG) to measure participants’ brain activity during task performance. Task relevance modulated the influence of predictions on behaviour: sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 72 publications
(137 reference statements)
8
84
0
Order By: Relevance
“…Such difference suggests that within-sequence repetitions are not a requirement for the learning process, as long as the sequence contains salient information to be learned. Both effects in our study were observed mostly in the beta band, which has been implicated in sensory memory (Haenschel et al, 2000;Scholz et al, 2017) and sensory predictions (Auksztulewicz and Friston, 2016;Auksztulewicz et al, 2017;Pearce et al, 2010).…”
Section: Discussionsupporting
confidence: 54%
“…Such difference suggests that within-sequence repetitions are not a requirement for the learning process, as long as the sequence contains salient information to be learned. Both effects in our study were observed mostly in the beta band, which has been implicated in sensory memory (Haenschel et al, 2000;Scholz et al, 2017) and sensory predictions (Auksztulewicz and Friston, 2016;Auksztulewicz et al, 2017;Pearce et al, 2010).…”
Section: Discussionsupporting
confidence: 54%
“…First, the two studies employed different behavioural tasks: participants performed orientation and contrast discrimination in Kok et al (2012a), whereas in the current study they discriminated grating phase. Although we do not have a clear hypothesis for how this would lead to differences in V1, previous work has shown that task demands influence expectation effects in visual cortex (50)(51)(52)(53). Additionally, there were differences in the grating presentations between the two studies.…”
Section: Discussionmentioning
confidence: 59%
“…Higher cortical regions implement top-down predictions in hierarchically lower cortical regions though synchronization of activity in lower-frequency ranges (i.e., the alpha/beta band), whereas prediction violations are propagated from lower to higher cortical regions through synchronization of gamma band activity (Arnal & Giraud, 2012;Michalareas et al, 2016). Indeed, a recent MEG study found that invalid predictions increased gamma activity induced by task-relevant stimuli in V1, however, not until 130ms after stimulus presentation (Auksztulewicz, Friston, & Nobre, 2017). Another MEG study employing a probabilistic cuing task also reported stimulus-induced increases in gamma-band activity by attention, which, in contrast to Auksztulewisz et al, decreased as a function of stimulus predictability (Bauer, Stenner, Friston, & Dolan, 2014).…”
Section: Discussionmentioning
confidence: 99%